Respuesta :
Hi,
Work:
Equation;
[tex] {4}^{2x + 3} = 1[/tex]
Write the number in exponential form with a base of 4.
[tex] {4}^{2x + 3} = 4^{0} [/tex]
Since the bases are the same, set the exponents equal.
[tex]2x + 3 = 0[/tex]
Move constant +3 to the right side and change its sign.
[tex]2x = - 3[/tex]
Divide both sides of equation by 2.
[tex]x = - \frac{3}{2} \: \: \: \: \: \: \: result \: (fraction) \\ \\ x = - 1.5 \: \: \: \: \: \: \: \: result \: (decimal)[/tex]
Hope this helps.
Work:
Equation;
[tex] {4}^{2x + 3} = 1[/tex]
Write the number in exponential form with a base of 4.
[tex] {4}^{2x + 3} = 4^{0} [/tex]
Since the bases are the same, set the exponents equal.
[tex]2x + 3 = 0[/tex]
Move constant +3 to the right side and change its sign.
[tex]2x = - 3[/tex]
Divide both sides of equation by 2.
[tex]x = - \frac{3}{2} \: \: \: \: \: \: \: result \: (fraction) \\ \\ x = - 1.5 \: \: \: \: \: \: \: \: result \: (decimal)[/tex]
Hope this helps.
[tex]4^{2x+3}=1\ \ \ \ \ |\log_4\\\\\log_44^{2x+3}=\log_41\\\\\boxed{use\ \log_a1=x\to x=0\ and\ \log_ab^n=n\log_ab}\\\\(2x+3)\log_44=0\\\\\boxed{use\ \log_aa=1}\\\\2x+3=0\ \ \ \ |-3\\\\2x=-3\ \ \ \ |:2\\\\\boxed{x=-1.5}[/tex]